2016
DOI: 10.4209/aaqr.2015.04.0278
|View full text |Cite
|
Sign up to set email alerts
|

Emission Profiles of PM10-Bound Polycyclic Aromatic Hydrocarbons from Biomass Burning Determined in Chamber for Assessment of Air Pollutants from Open Burning

Abstract: In order to estimate emission factors (EFs) of air pollutants, three types of biomass (rice straw, maize residue and leaf litter) were collected and burnt in a self-designed stainless steel chamber. The EFs of PM 10 from biomass burning were leaf litter (1.22 ± 0.29 g kg dry ). The results revealed that burning of forest leaf litter emitted higher amounts of particulate pollutants than the agricultural residue burning. New values of diagnostic ratios of some PAHs, including FLA/(FLA + PYR, BaA/(BaA + CHR) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 41 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…Enriched tracers from K + , NO 3 -and levoglucosan confirmed the major influence of biomass-burning activities, and the principal component analysis revealed that agricultural activities, soil re-suspension and road traffic were the additional sources of PM 2.5 over the sites. Furthermore, Wiriya et al (2016) thoroughly investigated and analyzed the emission factors of PM 10 and polycyclic aromatic hydrocarbons (PAHs) from the burning of leaf litter, maize residue and rice straw in a stainless steel chamber at CM site. They concluded that the burning of forest leaf litter emitted higher amounts of particulate pollutants than the agricultural residue burning.…”
Section: Atmospheric Compositionmentioning
confidence: 99%
“…Enriched tracers from K + , NO 3 -and levoglucosan confirmed the major influence of biomass-burning activities, and the principal component analysis revealed that agricultural activities, soil re-suspension and road traffic were the additional sources of PM 2.5 over the sites. Furthermore, Wiriya et al (2016) thoroughly investigated and analyzed the emission factors of PM 10 and polycyclic aromatic hydrocarbons (PAHs) from the burning of leaf litter, maize residue and rice straw in a stainless steel chamber at CM site. They concluded that the burning of forest leaf litter emitted higher amounts of particulate pollutants than the agricultural residue burning.…”
Section: Atmospheric Compositionmentioning
confidence: 99%
“…A number of studies have focused on atmospheric PAHs in developing nations such as China, India, Hong Kong, and Thailand (Chetwittayachan et al, 2002;Sun et al, 2004;Ravindra et al, 2006;Haggler et al, 2007;Liu et al, 2007;Okuda et al, 2010;Masih et al, 2012;Li et al, 2016;Pongpiachan, 2016;Wiriya et al, 2016;Yu et al, 2016;Tang et al, 2017;Zhou et al, 2017). Some studies have reported that vehicular emissions are the primary cause of PAH pollution in many Japanese cities (Chetwittayachan et al, 2002;Hayakawa, 2009;Murakami et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Suspended PM can be evaluated by its size. PM 10 (particles with aerodynamic diameter < 10 µm) has been associated with adverse health effects, although in recent times smaller cutoffs (PM 2.5 or PM 10 ) have been proposed as better indexes of air pollution owing to greater lung deposition of smaller particles in association with toxic compounds (Varghese and Gangemma, 2006;Wiriya et al, 2016). Since PAHs have affinity to the PM carbonaceous core, they are found mostly on smaller particles (Miguel et al, 1998;de Kok et al, 2005;Zhou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [12] worked on levels of PAHs in the different types of hospital waste incinerator ashes, their study linked the presence of organic matters in the waste to the level of PAHs in the residual ashes. Wiriya et al [13] studied emission profiles of PM 10 -bound PAHs from chamber burning of biomass.…”
Section: Introductionmentioning
confidence: 99%